Effective Integration of Young People into the Labor Market in Azerbaijan- Challenges in Transition from School to Work among Young People Aged Between 18-29 - Rustamova, Hilal; Hajiyev, Khayal; Hasanli, Ulkar (ADA University, 2024)
The purpose of this capstone project was to analyze and identify the main challenges in transition from school to work among young people aged between 18-29 in Azerbaijan. The study found out that geographical disparities between the capital city and other parts of the country, existence of non-meritocratic factors, lack of data center, lack of experience, skills mismatch, unequal access to career guidance are primary causes of youth unemployment. To solve the problem, certain policies were initiated to improve entrepreneurship, to decrease geographical disparities, to promote meritocratic factors in job admissions, to develop higher education and VEC education system, and to create data center.
Keywords: Youth -- Employment -- Azerbaijan.; School-to-work transition -- Azerbaijan.; Unemployment -- Causes -- Azerbaijan.; Labor market -- Azerbaijan.; Education -- Economic aspects -- Azerbaijan.